[Rezension von: Schipper, Jeremy, 1975-, Denmark Vesey's Bible : The Thwarted Revolt That Put Slavery and Scripture on Trial] - Egerton, Douglas R. 1956-; Schipper, Jeremy 1975- (2023)
In the Americas, enslaved rebels often carried a sword in one hand and a Bible or some type of religious object in the other. On the eve of the Haitian Revoluti